Indian politics in the twenty first century: electoral politics plus deliberative politics - the way forward - Satish Chandra, A. V. (New Delhi: Viva Books, 2017)
"In the modern period of human history, which is the true Common Era, democracy as a concept has attained not just acceptability but unprecedented sanctity by the time the 21st century came into being. However, the concept itself is not perfect even though people believe the construct of one-person- one-vote makes democracy truly representative. This book demonstrates to the contrary that as far as representing every person in society is concerned, democracy as we know it now is incapable of doing this. It is at best a majoritarian system where a winning candidate represents not just those who voted for that person but also those who voted against. This is a serious flaw that needs rectification. Otherwise a number of people in society go unrepresented or worse still represented by one whom they did not believe to be capable of being their representative. This book not only looks into how such a system has evolved over time and what are the difficulties that it creates. That means that not only does the book look into the positives but also the negatives that democracy in the present contains. It also goes on to prescribe changes and enhancements that can be made to the existing concept of democracy to make it better and more representative than it is today. In doing so it also puts the idea of education at the centre of things and demonstrates how a good education system can be used for the enhancement of representation in a democracy. So this book is as much a treatise about education as it is about democracy and politics and the shape they need to take in the 21st century."--Back cover.
Keywords: POLITICAL CULTURE-INDIA